Accessory middle turbinate accompanying a mucocele. Issue 2 (14th April 2013) - Lee, Dong‐Hoon; Joo, Young‐Eun; Lim, Sang‐Chul
<x xml:space="preserve">Abstract</x> Accessory middle turbinate is one of the rare anatomical variations of the nasal turbinate. To date, the accessory middle turbinate with an isolated pathological lesion has not been reported in the literature. A 62‐year‐old woman presented with the left‐sided nasal obstruction. An endoscopic examination showed a polypoid mass above the inferior turbinate. On magnetic resonance imaging, T2‐weighted imaging showed the cystic lesions of the left accessory middle turbinate and infratemporal fossa with isosignal intensity, compatible with accessory middle turbinate accompanying a mucocele. The patient underwent endoscopic sinus surgery, and the postoperative course was uneventful. In the present study, we report the first case of accessory middle turbinate accompanying a mucocele in a 62‐year‐old woman, and review the literature pertaining to this condition.